The Communicative Opportunities Afforded Parents of Premature Infants who had Graduated from a Neonatal Intensive Care Unit (NICU) - Crisp, Lynzi (My University, 2006)
This study endeavored to explore the opportunities afforded parents to develop optimal communication with their infants during their experience of the NICU in a private-sectored hospital. Six sets of parents participated in a semi-structured interview and completed a short questionnaire. They were interviewed one year after their infants were discharged from the NICU. The interview and questionnaire probed the three main components that are known to influence the development of optimal communication between parents and their infants in the Neonatal Intensive Care Unit (NICU): the infants prematurity and medical condition; the nature of the NICU; and the parents ability to adjust and adapt to the challenges faced during the NICU experience. The data obtained was analysed qualitatively using a constant comparative method. Six main themes emerged: preparedness; contact with the infant; bonding; information; support; and previous parenting experience. The findings reflected that the parents were afforded limited opportunities for the development of adequate infant-parent interaction. The implications of this study highlight the need for appropriate developmental and family-centred care to be implemented within NICUs in private-sector hospitals, the role of the speech-language therapist in the NICU team to be defined, and future research into the nature of the care provided within NICUs in South Africa.
Faculty of Speech,Language,Pathology and Audilogy School of Humanities and community Development 9604968n lynzicrisp@yahoo.co.uk
Keywords: Communication; Premature; Infants; Neonatal Intensive; care